1996
DOI: 10.1165/ajrcmb.15.5.8918370
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary artery NADPH-oxidase is activated in hypoxic pulmonary vasoconstriction.

Abstract: An NADPH-oxidase complex containing at least two protein components (gp91-phox and p22-phox) and a unique low redox potential (-245 mV) cytochrome b-245 is the source of superoxide generated for bacterial killing in neutrophils and has been suggested as the oxygen sensor in the carotid body. In pure cultures of smooth muscle cells from calf small pulmonary arteries (300 microns diameter) the presence of the 91 kD protein specific to this cytochrome was demonstrated by Western blot analysis with monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
187
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(201 citation statements)
references
References 50 publications
13
187
0
1
Order By: Relevance
“…Moreover, hypoxia-induced increases in the tissue level of superoxide and NADPH oxidase activity are potently suppressed by apocynin. As the support of our results, Marshall et al have shown that hypoxia increases superoxide production caused by NADPH oxidase in bovine arterial smooth muscle (36). Rathore et al have also demonstrated that hypoxia significantly increases NADPH oxidase activity by translocation of the cytosolic subunit to the plasma membrane in smooth muscle cells (37).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, hypoxia-induced increases in the tissue level of superoxide and NADPH oxidase activity are potently suppressed by apocynin. As the support of our results, Marshall et al have shown that hypoxia increases superoxide production caused by NADPH oxidase in bovine arterial smooth muscle (36). Rathore et al have also demonstrated that hypoxia significantly increases NADPH oxidase activity by translocation of the cytosolic subunit to the plasma membrane in smooth muscle cells (37).…”
Section: Discussionsupporting
confidence: 91%
“…This possibility warrants exploration in future studies. Recent studies have also identified a potentially major role for vascular cell-derived NAD(P)H oxidase in ROS formation (42,45,48). While not explored to any extent in the present study, our observations using in situ measurement of vascular ROS suggested that smooth muscle-derived NAD(P)H oxidase may be a major source of O 2 •Ϫ in the remodeled pulmonary vasculature.…”
Section: Discussionmentioning
confidence: 45%
“…Early theories on the subject suggested that NADPH oxidase might be an important ROS-generating cellular O 2 sensor since this multi-subunit membrane-bound enzyme is expressed in tissues implicated in systemic hypoxic responses and affects cellular redox status depending on cellular O 2 concentrations [69,70]. However more in-depth studies did not support a requirement for NADPH in the hypoxic adaptive response [71].…”
Section: Role Of Ros In Cellular O 2 Sensingmentioning
confidence: 99%